Tumor-Specific Fluorescent Antibody Imaging Enables Accurate Staging Laparoscopy in an Orthotopic Model of Pancreatic Cancer - Cao, Hop S Tran (2012)
BACKGROUND/AIMS: Laparoscopy is important in staging pancreatic cancer, but false negatives remain problematic. Making tumors fluorescent has the potential to improve the accuracy of staging laparoscopy. METHODOLOGY: Orthotopic and carcinomatosis models of pancreatic cancer were established with BxPC-3 human pancreatic cancer cells in nude mice. Alexa488-anti-CEA conjugates were injected via tail vein 24 hours prior to laparoscopy. Mice were examined under bright field laparoscopic (BL) and fluorescence laparoscopic (FL) modes. Outcomes measured included time to identification of primary tumor for the orthotopic model and number of metastases identified within 2 minutes for the carcinomatosis model. RESULTS: FL enabled more rapid and accurate identification and localization of primary tumors and metastases than BL. Using BL took statistically significantly longer time than FL. More metastatic lesions were detected and localized under FL compared to BL and with greater accuracy, with sensitivities of 96% vs. 40%, respectively, when compared to control. FL was sensitive enough to detect metastatic lesions <1mm. CONCLUSIONS: The use of fluorescence laparoscopy with tumors labeled with fluorophore-conjugated anti-CEA antibody permits rapid detection and accurate localization of primary and metastatic pancreatic cancer in an orthotopic model. The results of the present report demonstrate the future clinical potential of fluorescence laparoscopy.